Landscapes in Transition: A Study of Agricultural Land Use Change in Inner Terai of Nepal - Timilsina, R.H.; Ojha, G.P.; Nepali, P.B.; Tiwari, U. (International Journal of Social Sciences and Management, 2025)
Agricultural land use has raised concerns about the sustainability of locally led food systems. With urbanization in Chitwan district, cropland has been haphazardly used for different purposes. However, spatial-temporal cropland use changes in municipalities have not been explored. This research assesses the land use and land cover changes in six municipalities of Chitwan over two decades (2001 to 2021). Landsat images and the Google Earth platform were used to classify the land use. The study mainly focuses on the conversion of cropland to seven other land uses categories, and vice versa. The findings reveal a significant increase in built-up areas, particularly between 2011 and 2021, at the expense of agricultural land. The key drivers of these changes include the political system change notably the introduction of federalism and local governance in 2015, which has led to rapid migration, infrastructure development, and the expansion of urban centers. These land use changes pose challenges for sustainable agricultural land management, with cropland being replaced by built-up. Nevertheless, advancements in agricultural technologies have also converted other land use categories to cropland. This study emphasizes the urgent need for locally adaptable land use policies in line with national agricultural development strategies. The findings assist policymakers in developing sustainable land use strategies that maintain agricultural productivity while accommodating urban expansion. Timely intervention from the policy level is critical to protecting agricultural land and promoting a resilient, self-sufficient agricultural system in the face of ongoing urbanization and demographic changes. Int. J. Soc. Sc. Manage. Vol. 12, Issue-1: 46-59.